Synthesis of a new water-soluble hexacarboxylated tribenzotriquinacene derivative and its competitive host–guest interaction for drug delivery - Li, Man-Ping; Yang, Nan; Xu, Wen-Rong (Beilstein Journal of Organic Chemistry, 2022)
A new water-soluble hexacarboxylated tribenzotriquinacene derivative (TBTQ-CB6) was synthesized and used as a supramolecular drug carrier to load the model anticancer drugs dimethyl viologen (MV) and doxorubicin (DOX) via host–guest interactions. The drugs could be effectively released by spermine (SM), a molecule overexpressed in cancer cells, through host–guest competitive substitution since TBTQ-CB6 has a stronger binding affinity toward SM than MV and DOX. The host–guest interactions of the complexes of TBTQ-CB6 with MV, DOX and SM were investigated by NMR spectroscopy and fluorescence spectroscopy. The association stoichiometry of the complexes of TBTQ-CB6 with MV, DOX, and SM was found to be 1:1 with association constants of Ka = (7.67 ± 0.34) × 104 M−1, Ka = (6.81 ± 0.33) × 104 M−1, and Ka = (5.09 ± 0.98) × 105 M−1, respectively. The competitive substitution process was visualized by NMR titration. This novel TBTQ-based host–guest drug delivery system may have potential use in supramolecular chemotherapy.
Keywords: competitive substitution; drug delivery; host–guest chemistry; tribenzotriquinacene; water soluble

(untitled) - Bukowski, K.; Kciuk, M.; Kontek, R. (Int. J. Mol. Sci., 2020)

(untitled) - Chabner, B. A.; Roberts, T. G., Jr (Nat. Rev. Cancer, 2005)

(untitled) - Rivankar, S. (J. Cancer Res. Ther. (Mumbai, India), 2014)

(untitled) - Cannon, G. W.; Jackson, C. G.; Samuelson, C. O., Jr; Ward, J. R.; Williams, H. J.; Clegg, D. O. (Semin. Arthritis Rheum., 1985)

(untitled) - Kang, L.; Tian, Y.; Xu, S.; Chen, H. (J. Neurol., 2021)

(untitled) - Jones, R. (Medicine, 2016)

(untitled) - Senapati, S.; Mahanta, A. K.; Kumar, S.; Maiti, P. (Signal Transduction Targeted Ther., 2018)

(untitled) - Parveen, S.; Sahoo, S. K. (J. Drug Targeting, 2008)

(untitled) - Pugazhendhi, A.; Edison, T. N. J. I.; Karuppusamy, I.; Kathirvel, B. (Int. J. Pharm., 2018)

(untitled) - Raza, A.; Hayat, U.; Rasheed, T.; Bilal, M.; Iqbal, H. M. N. (J. Mater. Res. Technol., 2019)

(untitled) - Chen, Y.; Sun, Z. (ACS Appl. Bio Mater., 2020)

(untitled) - Webber, M. J.; Langer, R. (Chem. Soc. Rev., 2017)

(untitled) - Zheng, Z.; Geng, W.-C.; Xu, Z.; Guo, D.-S. (Isr. J. Chem., 2019)

(untitled) - Chen, J.; Zhang, Y.; Zhao, L.; Zhang, Y.; Chen, L.; Ma, M.; Du, X.; Meng, Z.; Li, C.; Meng, Q. (ACS Appl. Mater. Interfaces, 2021)

(untitled) - Zhang, Z.; Yue, Y.-X.; Xu, L.; Wang, Y.; Geng, W.-C.; Li, J.-J.; Kong, X.-l.; Zhao, X.; Zheng, Y.; Zhao, Y.; Shi, L.; Guo, D.-S.; et al. (Adv. Mater. (Weinheim, Ger.), 2021)

(untitled) - Xing, P.; Zhao, Y. (Small Methods, 2018)

(untitled) - Chen, Y.; Huang, Z.; Zhao, H.; Xu, J.-F.; Sun, Z.; Zhang, X. (ACS Appl. Mater. Interfaces, 2017)

(untitled) - Chen, Y.; Huang, Z.; Xu, J.-F.; Sun, Z.; Zhang, X. (ACS Appl. Mater. Interfaces, 2016)

(untitled) - Yang, J.; Dai, D.; Ma, L.; Yang, Y.-W. (Chin. Chem. Lett., 2021)

(untitled) - Hao, Q.; Chen, Y.; Huang, Z.; Xu, J.-F.; Sun, Z.; Zhang, X. (ACS Appl. Mater. Interfaces, 2018)

(untitled) - Kuck, D. (Chem. Rev., 2006)

(untitled) - Wang, T.; Li, Z.-Y.; Xie, A.-L.; Yao, X.-J.; Cao, X.-P.; Kuck, D. (J. Org. Chem., 2011)

(untitled) - Bredenkötter, B.; Henne, S.; Volkmer, D. (Chem. – Eur. J., 2007)

(untitled) - Bredenkötter, B.; Grzywa, M.; Alaghemandi, M.; Schmid, R.; Herrebout, W.; Bultinck, P.; Volkmer, D. (Chem. – Eur. J., 2014)

(untitled) - Henne, S.; Bredenkötter, B.; Alaghemandi, M.; Bureekaew, S.; Schmid, R.; Volkmer, D. (ChemPhysChem, 2014)

(untitled) - Henne, S.; Bredenkötter, B.; Dehghan Baghi, A. A.; Schmid, R.; Volkmer, D. (Dalton Trans., 2012)

(untitled) - Georghiou, P. E.; Dawe, L. N.; Tran, H.-A.; Strübe, J.; Neumann, B.; Stammler, H.-G.; Kuck, D. (J. Org. Chem., 2008)

(untitled) - Wang, X.-R.; Li, M.-P.; Xu, W.-R.; Kuck, D. (Asian J. Org. Chem., 2021)

(untitled) - Liu, S.-Y.; Wang, X.-R.; Li, M.-P.; Xu, W.-R.; Kuck, D. (Beilstein J. Org. Chem., 2020)

(untitled) - Frassineti, C.; Alderighi, L.; Gans, P.; Sabatini, A.; Vacca, A.; Ghelli, S. (Anal. Bioanal. Chem., 2003)

(untitled) - Weisell, J.; Hyvönen, M. T.; Häkkinen, M. R.; Grigorenko, N. A.; Pietilä, M.; Lampinen, A.; Kochetkov, S. N.; Alhonen, L.; Vepsäläinen, J.; Keinänen, T. A.; Khomutov, A. R. (J. Med. Chem., 2010)

(untitled) - Kamieth, M.; Klärner, F.-G.; Diederich, F. (Angew. Chem., Int. Ed., 1998)

(untitled) - Yu, G.; Zhao, R.; Wu, D.; Zhang, F.; Shao, L.; Zhou, J.; Yang, J.; Tang, G.; Chen, X.; Huang, F. (Polym. Chem., 2016)